Armenian Architecture of Crimea of the 13th–15th Centuries. The Issue of Boundaries between National and Confessional Traditions on the Peninsula - Kazaryan, Armen (Actual Problems of Theory and History of Art, 2019)
Armenian medieval architecture of the Crimean peninsula is a phenomenon that has been largely studied in terms of building a factual database, identifying the church typology, and discovering national roots of the local tradition. However, those studies have not actually considered Armenian medieval heritage to be apart of a regional phenomenon that united building traditions of several peoples in the 13th–15th centuries.The very existence of such a cumulative concept as the Crimean medieval architecture forces us to raise the questionof the development of some individual national/confessional traditions within it, as well as the question of boundaries between national styles of architecture on the peninsula. The present historical and theoretical research aims to give a new impetus for the discussion of these interconnected issues basing on comparative analysis of the monuments of Armenian architecture. It becomes obvious that the forms of arches and vaults, capitals and cornices, domes and portals of the Armenian churches not only resemble some patterns of the architecture of Armenia itself, but also show similarities with the churches of other confessions, particularly Genoese, as well as with mosques and mausoleums built on the orders of the Golden Horde rulers. Most likely these interconnections existed due to the following factors: 1) common cultural environment on the Crimean peninsula; 2) developing fashion for architectural forms and decor; 3) work of the same masters on buildings of different confessions (the last thesis is not developed in the article). The study deduces that the boundaries between national styles do not lie in the field of architectural forms and ornaments. However, they do exist and they should be identified when exploring the composition of buildings, as it is the composition that determined the originality of architectural images.